Comparison of the effectiveness of platelet rich plasma and ozone therapy in plantar fasciitis treatment - Yalcin, Umit (International Journal of Research in Medical Sciences, 2020)
Background: Plantar fasciitis (PF) is one of the most common foot problems in adults. Conservative treatments are proportionally 90-95% successful. In this study, author aimed to compare the effectiveness of ozone therapy (OT) treatment of platelet rich plasma (PRP) injections in PF patients. Methods: In the study, which was made prospectively, patients were randomly divided into two groups. In the first group (n=20), patients were injected with PRP in 3 sessions at a one week intervals, and in the second group (n=22) OT was injected in the same way. Each patient was evaluated with visual pain score before as well as 1 month after treatment in terms of pain, whereas the foot function index (FFI) was evaluated with the score in terms of functionality. Results: In both groups, the 1st month VAS score and FFI score showed significant decrease (p<0.05) after treatment compared to before treatment. The decrease in VAS score and FFI score after treatment in the PRP group was significantly higher than the OT group (p˂0.05). Conclusions: As a result of this study, authors found that both PRP and OT were beneficial in terms of pain and functional level in the treatment of PF, but in patients who underwent PRP, authors found that there was more statistical improvement in terms of both parameters than patients who received OT. In light of the absence of a previous publication comparing these two treatment options in PF treatment, this study contributes to the literature.